Well, honey, you just add those like terms together. 5x plus x is the same as 6x. It's as simple as that, darling.
y-5x
3(x+y)
2x plus 5x simplified is 7x.
5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y
3x^2 + x + 2x^2 = 5x^2 + x
5x - 4x = x
Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x
Set up the equation and then solve: 5x + 2 = 6 + x (next, get like terms together) 5x - x = 6 - 2 (next, simplify) 4x = 4 (next divide both sides by 4 to solve for x) x = 1
-3
It is: 12x
5x - 8a + 4a - 2x + a = 3x - 3a
To simplify the expression 18 + 7x - 12 + 5x, you first combine like terms. Combine the constants (18 and -12) to get 6. Then, combine the x terms (7x and 5x) to get 12x. Therefore, the simplified expression is 6 + 12x.